Effect of Bifidobacterium animalis subsp. lactis Langg JZ-08 on lipid metabolism in individuals with obesity and dyslipidemia: A randomised, double-blind, and placebo-controlled trial - Xiaokang Niu; Qi Zhang; Yong Zhang; Ran Wang; Kai Yao; Yue Sang; Bing Fang; Yuyang Zhao; Liwei Liu; Langrun Wang; Rong Liu; Yixuan Li; et al. (Human Nutrition & Metabolism)
Dyslipidemia is an established risk factor for cardiovascular disease, especially for individuals with obesity. Probiotics have been studied for their potential lipid-lowering properties, but the evidence in individuals with obesity and dyslipidemia is limited. For trial feasibility purposes, this study explored the effects of Bifidobacterium animalis subsp. lactis Langg JZ-08 (Langg JZ-08) on lipid metabolism in individuals with obesity and dyslipidemia. In a randomized, double-blind, placebo-controlled pilot trial, 40 individuals (7 males and 13 females in the placebo group, 10 males and 10 females in the probiotic group) with obesity and dyslipidemia, aged 18–65 years consumed daily probiotics (5 × 1010 CFU/day Langg JZ-08) or placebo for 12 weeks. Body composition, blood lipids, markers of glycometabolism, antioxidants, and inflammation were measured before and after the intervention. Langg JZ-08 consumption significantly decreased low-density lipoprotein cholesterol (P = 0.01), body fat percentage (P = 0.01), visceral fat area (P = 0.04), serum insulin (P = 0.01), glycosylated hemoglobin (P = 0.02), tumor necrosis factor-α (P < 0.05), and increased glutathione peroxidase (GPX) (P < 0.001) and total antioxidant capacity (T-AOC) (P < 0.01) compared to the baseline. The decrease in total cholesterol was significantly greater in the probiotic group than in the placebo group after 12 weeks of intervention (P = 0.04). After the intervention, the serum superoxide dismutase, GPX and T-AOC levels were significantly higher in the Langg JZ-08 group than that of the placebo group (P < 0.05). There were no significant inter- and intra-group differences in triglycerides, high-density lipoprotein cholesterol, body mass index, waist, hip, and fasting blood glucose after the intervention. 12-week Langg JZ-08 intervention improved lipid metabolism, oxidative stress, and inflammation in individuals with obesity and dyslipidemia. This pilot trial supports the feasibility of a larger scale randomized controlled trial to determine the efficacy of Langg JZ-08 on obesity with dyslipidemia.